Current Level and Correlates of Traditional Cooking Energy Sources Utilization in Urban Settings in the Context of Climate Change and Health, Northwest Ethiopia: A Case of Debre Markos Town. (7th May 2014) - Geremew, Kumlachew; Gedefaw, Molla; Dagnew, Zewdu; Jara, Dube
Abstract : Background. Traditional biomass has been the major source of cooking energy for major segment of Ethiopian population for thousands of years. Cognizant of this energy poverty, the Government of Ethiopia has been spending huge sum of money to increase hydroelectric power generating stations. Objective. To assess current levels and correlates of traditional cooking energy sources utilization. Methods. A community based cross-sectional study was conducted employing both quantitative and qualitative approaches on systematically selected 423 households for quantitative and purposively selected 20 people for qualitative parts. SPSS version 16 for windows was used to analyze the quantitative data. Logistic regression was fitted to assess possible associations and its strength was measured using odds ratio at 95% CI. Qualitative data were analyzed thematically. Result. The study indicated that 95% of households still use traditional biomass for cooking. Those who were less knowledgeable about negative health and environmental effects of traditional cooking energy sources were seven and six times more likely to utilize them compared with those who were knowledgeable (AOR (95% CI) = 7.56 (1.635, 34.926), AOR (95% CI) = 6.68 (1.80, 24.385), resp.). The most outstanding finding of this study was that people use traditional energy for cooking mainly due to lack of the knowledge and their beliefs about food prepared using traditional energy. That means "…people still believe that food cooked with charcoal is believed to taste delicious than cooked with other means."   Conclusion. The majority of households use traditional biomass for cooking due to lack of knowledge and belief. Therefore, mechanisms should be designed to promote electric energy and to teach the public about health effects of traditional cooking energy source.